2022
DOI: 10.14202/vetworld.2022.435-441
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effects of CSN1S1 and CSN2-casein genes on Awassi sheep milk quantity and quality

Abstract: Background and Aim: Milk produced from Awassi sheep is of high nutritive value; its production is relatively low in Awassi sheep, so the genetic improvement programs targeted milk production and its components are of high importance, especially when using genes that have an important signal to milk traits. This study was aimed at assessing the influence of alpha S1 (CSN1S1) and beta-casein (CSN2) genes genotypes interaction on Awassi ewes milk productivity. Materials and Methods: A total number of 391 milk yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…According to our investigation, the interactions of the BLG|CSN3, BLG|CSN1S1, PRL|CSN2, PRL|CSN3, CSN2|CSN1S1, and PRL|CSN2|CSN1S1 genotypes significantly impacted the EBVs of milk production in Awassi sheep (Figures -2a-e and-3). Similarly, Jawasreh et al [14] and Al-Amareen and Jawasreh [21] both reported a significant effect of the BLG|PRL and CSN1S1|CSN2 genotypes on milk production in Awassi sheep.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…According to our investigation, the interactions of the BLG|CSN3, BLG|CSN1S1, PRL|CSN2, PRL|CSN3, CSN2|CSN1S1, and PRL|CSN2|CSN1S1 genotypes significantly impacted the EBVs of milk production in Awassi sheep (Figures -2a-e and-3). Similarly, Jawasreh et al [14] and Al-Amareen and Jawasreh [21] both reported a significant effect of the BLG|PRL and CSN1S1|CSN2 genotypes on milk production in Awassi sheep.…”
Section: Discussionmentioning
confidence: 79%
“…Researchers worldwide have investigated different potential genes that substantially impact milk production in sheep [ 14 , 19 , 20 , 21 ]. These genes include CSN3 , CSN1S1 , CSN2 , BLG , and PRL .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations